Physiological stress in cattle as a response to coexistence with wildlife in ecological interaction zones in the province of Pastaza, Ecuador (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Ecuador has great biological diversity, including large carnivores that generate conflicts with livestock farming. In Pastaza, physiological stress in cattle coexisting with wildlife was evaluated through cortisol measurement. Fifty cattle were selected — 25 from conflict zones and 25 from non-conflict zones — sampled in Veracruz, El Triunfo, 10 de Agosto, Shell, and Fátima. Blood samples were collected at two different times and processed in the Biology 1 Laboratory of the Universidad Regional Amazónica IKIAM. Cortisol levels were quantified using a fluorescence immunoassay (i-CHROMA™), and health status was assessed by measuring C-reactive protein (CRP). Cattle exposed to carnivores showed significantly higher levels of cortisol and CRP, indicating inflammation caused by chronic stress that affects immunity, welfare, and productivity. The study highlights the need for management strategies that promote coexistence between livestock farming and conservation.